Value Polarization as A Mediating Mechanism Between Economic Uncertainty and Sustainable Financial Decisions - Kadek Wulandari Laksmi P; Komang Widhya Sedana Putra P; IGN Oka Ariwangsa (Business Management Analysis Journal (BMAJ), 2026)
Economic uncertainty has become an unavoidable feature of contemporary economic life, intensifying pressure on financial decision-makers to balance short-term stability with long-term sustainability. Despite growing attention to sustainable finance, prior studies report inconsistent findings regarding the effect of economic uncertainty on sustainability-oriented financial decisions, leaving a critical gap in understanding the underlying mechanism. To address this gap, this study examines the mediating role of value polarization in the relationship between economic uncertainty and sustainable financial decision-making. Using a quantitative approach, data were collected through a structured survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that economic uncertainty does not directly influence sustainable financial decision-making but significantly intensifies value polarization, which in turn shapes sustainability-oriented financial outcomes. These findings highlight the importance of value-based processes in explaining heterogeneous financial behavior under uncertainty. Future research may extend this model by incorporating longitudinal designs or institutional factors to capture dynamic value shifts across different economic contexts.